Implementasi Sistem Monitoring Kualitas Air Kolam Lele menggunakan Komunikasi Bluetooth Low Energy (BLE) berdasarkan Parameter Suhu dan PH - Rizqi Agung Dwi Nugraha; Rakhmadhany Primananda; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Indonesia is one of the largest fish producing countries in the world. One of the fish that is in demand in Indonesia from various circles of society is catfish. Therefore, the way to increase catfish production is to maintain the quality of pond water used for catfish farming. The quality of water used for catfish farming is very influential on the growth of catfish. Using a monitoring system can help to monitoring the water quality of catfish ponds so that catfish growth can be optimal. In this study, a catfish pond water quality monitoring system was created which consists of three nodes slave and one node master and uses a webserver as an interface. Each node slave has two sensors, a temperature sensor and a pH sensor that functions as a detector of water quality in the pond. Communication between nodes slave and node master uses the BLE communication protocol. while for the webserver to run on the master node using WiFi communication. The microcontroller for this system uses NodeMCU ESP32. Based on the test results, the average system accuracy in reading the water temperature of the catfish pond is 97.88%, the average system accuracy in reading the pH of the pond water is 98.53%. The farthest BLE communication is 25 meters with a delay of 2815.8 ms for BLE communication and 252.4 ms for the webserver.